ANALYSIS OF FACTORS IMPROVING EMPLOYEE PERFORMANCE - Dongoran, Faisal Rahman (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
The objectives of this research are: to determine and analyze the factors that affect employee performance at PT Harian Waspada medan. This study was conducted using an associative approach. Sampling is done by non probability sampling technique with saturated sampling type so that all 54 employees are used as samples. All hypotheses accepted in this research based on the results of the analysis showed that simultaneously and partially creativity and discipline have a positive and significant effect on performance.